Nilai Kalor Briket Limbah Kayu Sengon Dengan Perekat Maizena Lebih Tinggi Di Bandingkan Tapioka, Sagu Dan Tepung Singkong - Arifin, Zainal; ., Hantarum; Nuriana, Wahidin (JURNAL PILAR TEKNOLOGI : Jurnal Ilmiah Ilmu Ilmu Teknik, 2018)
Bio-briquette is a solid fuel made from organic waste and mixed with other ingredients and then printed using certain pressures so that the desired shape and characteristics are obtained. This study focused on determining the effect of adhesive on density, moisture content and heating value on sengon wood charcoal bio-briquette with variations of tapioca, sago, cornstarch and cassava flour with a pressure of 115 kg / . The results showed that the highest density was 0.56 g/ in the bio-briquette of sengon wood waste charcoal with cassava flour adhesive, the lowest water content was 6.52% in the bio-briquette of sengon wood waste with cornstarch adhesive and the highest heating value was found in briquettes maizena adhesive sengon wood waste is 5,868 cal / gr.Â Keywords: sengon wood waste briquettes, adhesive, density, moisture content and heating value